2015
DOI: 10.5812/ircmj.20596
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Clinical Judgment Development: A Qualitative Research in Iran

Abstract: Background:Clinical judgment development is necessary because it leads to appropriate nursing diagnoses, clinical decision-making and health promotion.Objectives:In this study we explored the process of Iranian nurses’ development in clinical judgment.Patients and Methods:This qualitative study was conducted in 2013 at hospitals of Kurdistan University of Medical Sciences, located in the Sanandaj city of Iran. The data were collected based on semi-structured interviews and the study included 24 participants. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
0
16
0
4
Order By: Relevance
“…North Carolina showed that the greatest dissatisfaction of patients was due to disrespect, failure to meet medical expectations, providing inadequate information to the patient, lack of timely access to the physician, lack of inter-professional communication, lack of information provision and distrust with the physician (All of these categories were among the indicators in the questionnaire in the present study) [31]. It appears that the patient-physician relationship is one of the main factors associated with patient satisfaction [16,20]. In addition to the above, the results of oneway ANOVA showed that patients who had a longer visit to a physician had a higher degree of satisfaction (α=0.05).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…North Carolina showed that the greatest dissatisfaction of patients was due to disrespect, failure to meet medical expectations, providing inadequate information to the patient, lack of timely access to the physician, lack of inter-professional communication, lack of information provision and distrust with the physician (All of these categories were among the indicators in the questionnaire in the present study) [31]. It appears that the patient-physician relationship is one of the main factors associated with patient satisfaction [16,20]. In addition to the above, the results of oneway ANOVA showed that patients who had a longer visit to a physician had a higher degree of satisfaction (α=0.05).…”
Section: Resultsmentioning
confidence: 93%
“…Interpersonal aspects of care, including physician's attitudes and communication are considered the main components of patient satisfaction. Since patient's satisfaction with the treatment process provides the motivation for continuing treatment and timely and correct use of medical prescriptions, which will ultimately lead to the acceleration of recovery and health on the one hand, and the achievement of a positive image of the existing therapeutic process on the other hand [20], it can be concluded that patient satisfaction survey is of particular importance. Diabetes is a chronic disease of a particular concern to the health system for several reasons, including the spread of disease, complications, and the high costs of care and treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse sentido, estudo iraniano verificou que enfermeiros mais experientes, com maior tempo de trabalho na área assistencial, utilizam, predominantemente, o raciocínio clínico não-analítico para a tomada de decisões, pois confiam em suas habilidades de reconhecer padrões. Atestou, ainda, que os enfermeiros recém-formados, valem-se do raciocínio clínico analítico, devido à insegurança e falta de experiências clínicas suficientes a ponto de permitir o reconhecimento de padrões 17 . Paralelamente, estudo australiano constatou que os profissionais com maior tempo de experiência clínica possuem raciocínio clínico acurado e ágil, enquanto que aqueles que têm pouco tempo de experiência apresentam dificuldades para coletar dados do histórico de saúde e integrá-los aos seus conhecimentos científicos, lentificando o processo de raciocínio clínico 13 .…”
Section: Desenvolvimento E Aprimoramento Do Raciocínio Clínicounclassified
“…Ao decorrer de sua trajetória assistencial, o enfermeiro vivencia e processa muitas informações clínicas semelhantes, as quais, geralmente, levam à determinação de cuidados parecidos 17 . Assim, pode-se inferir que o processamento repetido dessas informações pelo sistema 2 de raciocínio proporciona o reabastecimento dos padrões reconhecidos pelo sistema 1, fazendo com que essas informações sejam rapidamente reconhecidas e processadas pelo sistema não-analítico, nas próximas vezes que forem vivenciadas.…”
Section: Desenvolvimento E Aprimoramento Do Raciocínio Clínicounclassified